Dispositional Characteristics of Individuals Involved in Back Burner Relationships. Issue 4 (2nd October 2017) - Borzea, Dana; Dillow, Megan R.
Abstract : To determine whether certain characteristics are shared by young adults who choose to communicatively maintain back burner relationships, this study investigated the associations between dispositional characteristics (i.e., sociosexual orientation, sensation seeking, narcissism, Machiavellianism, and the Big Five personality traits) and the number of back burners maintained by single and romantically involved individuals. Findings revealed that all dimensions of unrestricted sociosexual orientation and high sensation seeking were positively associated with number of back burners when predictors were considered independently. When the relative contribution of predictors was examined, only unrestricted sociosexual behavior significantly predicted the number of back burners. Implications for developing a profile of those who communicate to initiate and sustain back burner relationships are discussed.